Reciprocal relations between care-related emotional burden and sleep problems in healthcare professionals: a multicentre international cohort study. Issue 9 (19th July 2018) - Cheval, Boris; Mongin, Denis; Cullati, Stéphane; Winz, Carole; von Arx, Martina; Schmidt, Ralph Erich; Agoritsas, Thomas; Chopard, Pierre; Courvoisier, Delphine Sophie
Abstract : Objective: To determine whether there are reciprocal relations between care-related regret and insomnia severity among healthcare professionals, and whether the use of different coping strategies influences these associations. Methods: This is a multicentre international cohort study of 151 healthcare professionals working in acute care hospitals and clinics (87.4% female; mean age=30.4±8.0 years, 27.2% physicians, 48.3% nurses and 24.5% other professions) between 2014 and 2017. Weekly measures of regret intensity, number of regrets, and use of coping strategies (Regret Coping Scale) and sleep problems (Insomnia Severity Index) were assessed using a web survey. Results: The associations between regret and insomnia severity were bidirectional. In a given week, regret intensity (bregret intensity→sleep =0.26, 95% credible interval (CI) (0.14 to 0.40)) and number of regrets (bnumber of regrets→sleep =0.43, 95% CI (0.07 to 0.53)) were significantly associated with increased insomnia severity the following week. Conversely, insomnia severity in a given week was significantly associated with higher regret intensity (bsleep→regret intensity =0.14, 95% CI (0.11 to 0.30)) and more regrets (bsleep→number of regrets =0.04, 95% CI (0.02 to 0.06)) the week after. The effects of regret on insomnia severity were much stronger than those in the opposite direction. The use of coping strategies, especially if they were maladaptive, modified the strength of these cross-lagged associations. Conclusions: The present study showed that care-related regret and sleep problems are closely intertwined among healthcare professionals. Given the high prevalence of these issues, our findings call for the implementation of interventions that are specifically designed to help healthcare professionals to reduce their use of maladaptive coping strategies.